The effect of physical exercise on the anxiety of college students in the post-pandemic era: The mediating role of social support and proactive personality - Liu, Mengfan; Shi, Bo (Frontiers in Psychology, 2023)
In order to study the current situation of the anxiety of college students in the post-pandemic era and the effect of physical exercise on anxiety, this study explores the influence of social support and proactive personality as mediating variables on the anxiety of college students from the perspective of physical exercise. Firstly, anxiety symptoms and anxious emotions are defined. Secondly, a questionnaire survey is conducted for a well-known university in a certain city, and different questionnaire scales are developed from the physical exercise, anxiety, social support, and proactive personality assessment of college students. Finally, the results of the survey are statistically analyzed to explore the relieving effect of physical exercise on anxiety. The results reveal that there is a significant gender difference in the level of physical exercise, and the amount of physical exercise of the male students is generally higher than that of female students. In addition, the intensity, time, and frequency of exercise of male students are more than that of female students, but there is no obvious difference between them and whether they were only children. Physical exercise habits, social support, proactive personality traits, and anxiety of college students have a significant correlation. Through the analysis of the chain mediation effect, Ind2(0.0140) is the largest coefficient among the three paths, indicating that the path of influencing social support through physical exercise habits, followed by affecting proactive personality traits, and then impacting anxiety has the strongest explanatory force. According to the results, strategies to relieve the anxiety of college students are given. This study can provide a reference for the research on the methods to alleviate their anxiety under the influence of the epidemic.